CRANIOFACIAL MORPHOLOGY OF HUMAN REMAINS FROM ANCIENT BURIALS OF TSUVRAA MOUNTAIN, IN UGUUMUR AREA, KHULENBUIR SUM, DORNOD AIMAG, MONGOLIA - Д.ТҮМЭН (Mongolian Journal of Anthropology, Archaeology and Ethnology, 2002)
The Paleoanthropological study of human remains from different prehistoric archaeological sites of Mongolia play an important role in solving the problem not only of the origin of Mongols, but the problem of prehistoric migrations and biocultural and historical relationship of ancient populations from Northeast Asia. The goals of the paleoanthropological study are 1). To carry out craniological, studies of human remains obtained from archaeological excavation carried out in Eastern Mongolia: 2). To conduct comparative morphological analysis for ancient populations prom Eastern Mongolian and Northeast Asian based on obtained craniofacial data on the ancient Mongolian populations In the paper is given main results of craniological study of human remains discovered during archaeological excavations in Eastern Mongolia in 2002.